Evaluation of Winter Wheat Genotypes for Weed Competitiveness and Yield under Organic Production Management. Issue 1 (1st July 2014) - Karki, David; Hall, Jesse; Mueller, Nathan; Sexton, Peter
Abstract : Weed management imposes the largest constraint on field crop production under organic management systems. Research was conducted to identify winter wheat genotypes with good yield potential that are competitive with weeds for use in organic systems. Thirty winter wheat genotypes were evaluated over two years for ability to compete against weeds and for grain yield production in southeastern South Dakota. Genotypes evaluated showed significant differences in suppression of weed production and in grain yield performance; however, genotype‐by‐season interaction was significant suggesting that different environmental conditions between the two seasons influenced genotype rankings. Weed biomass showed a negative relationship with crop shoot biomass. Certain released cultivars (Jerry and Scout66 winter wheat) and advanced breeding lines (NE03490 winter wheat, and NE42G2T and NT01451 winter triticale) showed promising results in terms of weed suppression and acceptable grain yield.